THE USES OF MYTH AND RITUALS AS COMMUNICATION STRATEGIES FOR ENVIRONMENTAL PRESERVATION BY KRATON NGIYOM IN SEKARALAS AND SEKARPUTIH VILLAGES - Parani, Rizaldi; Berliana, Brigitta; Putri, Liza Diniarizky; Annisarizki, Annisarizki; Malik, Abdul (HUMANIKA, 2021)
Kraton Ngiyom is a non-profit organization that focuses on environmental preservation. To overcome the environmental problems in the villages of Sekaralas and Sekarputih, Ngawi, East Java, especially regarding the condition of damage to the forest area and both springs in the village area, Kraton Ngiyom uses communication strategies based on local wisdom by utilizing mythologically oriented instrument and ceremonies as a medium of communication to encourage the public to care and actively contribute in carrying out environmental preservation activities. This study aims to answer the research question of how the Kraton Ngiyom uses myth and rituals as communication strategies for environmental conservation in the villages of Sekaralas and Sekarputih. This study employs an ethnographic study approach. Data collection was carried out using direct observation and in-depth interviews with five informants. The results of this study found that the communication strategies based on local wisdom are well implemented by Kraton Ngiyom through 2 instruments, namely myths and rituals. The myth is used by Kraton Ngiyom to deliver environmental preservation messages to the people of Sekaralas and Sekarputih villages, while the rituals are used by Kraton Ngiyom as instruments to support the delivery of messages, which is to encourage changes in village community behavior. The process of delivering messages through myths, which was maximized in the implementation of a ceremony, succeeded in changing the behavior of Sekaralas and Sekarputih villagers to become more concerned about their environmental conditions and to take initiatives in undertaking environmental conservation efforts.